INNOVATIONS IN TEACHING LISTENING SKILLS FOR IELTS AND CEFR: EMBRACING MODERN METHODS - Alimardonova Maftuna Bekmurodovna (Journals Park Publishing, 2024)
This article delves into progressive strategies for improving listening skills tailored for IELTS and CEFR exams. It highlights the integration of technology, authentic materials, interactive activities, and self-assessment to enhance comprehension.
Keywords: Teaching, Listening Skills, IELTS, CEFR, Innovations, Modern Methods.